Optogenetic Termination of Cardiac Arrhythmia: Mechanistic Enlightenment and Therapeutic Application? - Sasse, Philipp; Funken, Maximilian; Beiert, Thomas; Bruegmann, Tobias (Frontiers in Physiology, 2019)
Optogenetic methods enable selective de- and hyperpolarization of cardiomyocytes expressing light-sensitive proteins within the myocardium. By using light, this technology provides very high spatial and temporal precision, which is in clear contrast to electrical stimulation. In addition, cardiomyocyte-specific expression would allow pain-free stimulation. In light of these intrinsic technical advantages, optogenetic methods provide an intriguing opportunity to understand and improve current strategies to terminate cardiac arrhythmia as well as for possible pain-free arrhythmia termination in patients in the future. In this review, we give a concise introduction to optogenetic stimulation of cardiomyocytes and the whole heart and summarize the recent progress on optogenetic defibrillation and cardioversion to terminate cardiac arrhythmia. Towards this aim, we specifically focus on the different mechanisms of optogenetic arrhythmia termination and how these might influence the prerequisites for success. Furthermore we critically discuss the clinical perspectives and potential patient populations which might benefit from optogenetic defibrillation devices.